آليات تحسين وترشيد الخدمة العمومية - بن عوالي, بوبكر (My University, 2017)
الجزائر كباقي الدول تسعى دوما إلى مسايرة التطور و هذا ما فرض عليها تغير في سياساتها و تدعيم مخططاتها لمجابهة التطور الكبير و المستمر لعالم تغلب عليه العولمة و الصراعات وحتى تكون في الصدارة عليها أن تهتم بمواطنيها لأن أي دولة أساس حكمها الشعب و حتى يكون أهل لذلك يجب أن يكون شعب راق و متحضر وحتى يكون كذلك يجب أن يتمتع بكل حقوقه و مطلبه الأول هو الخدمة العمومية . لكي تكون الخدمة العمومية في مستوي جيد يجب أن نوفر لها آليات جادة ، حتى تقوم هذه الآليات العمل المنوط بها ندعمها بالقوانين و اللوائح و الأحكام التي تعطيها و تكسبها المصداقية و حسن الأداء و الحماية القانونية و هذا يجب أن يكون تحت سلطة حكم سليم و قوي ما يعرف بالحكم الراشد الذي بقيامه و إتحاد مكوناته الثلاث من سلطة قوية بمؤسساتها ومجتمع مدني متحضر وقطاع خاص الشريك الأساسي للدولة ، وعليه الحكم الراشد آلية هامة يساهم في تسير الدولة بهياكلها و مؤسساته قوية و صامدة لتقديم أحسن للخدمة العمومية . يعد المرفق العام أهم ركيزة لتقديم الخدمة العمومية إذا أقيمة أركانه و تكييفه مع التطور التكنولوجي و ذلك لزيادة طلبات مستعملي المرفق العام و حاجياتهم ، حتى تكون الخدمة راقية يجب العمل على جودة الخدمات المقدمة من طرف المرفق العام وتوفير كل العوامل و الوسائل اللازمة لخدمة أفضل . كي تعمل هذه الآليات عملها على أكمل وجه يستدعي استعمال و تطبيق الإدارة الإلكترونية التي تعد آلية لتطوير الإدارة و المرفق العام و تقريب الإدارة من الموطن و تسهيل المعاملات الإدارية و تعمل بصفة كبيرة في تحسين الخدمة العمومية . Algeria, like all other countries, is always striving to keep pace with development, and this is what has been imposed on it by changing its policies and strengthening its plans to confront the great and continuous development of a world dominated by globalization and conflicts and to be at the forefront of it, to take care of its citizens. To be a civilized and civilized people and even to be so must enjoy all his rights and his first demand is the public service. In order for the public service to be a good level, we must provide it with serious mechanisms, so that these mechanisms work with us to support them with the laws, regulations and provisions that give them and gain credibility, good performance and legal protection. This must be under the authority of a sound and strong government. It is known for its strong governance and the unity of its three components. It has strong authority in its institutions, civil society and private sector, the main partner of the state, and it is an important mechanism that contributes to the state's strong structures and institutions. The General Facility is the most important pillar for the provision of public services if the value of its facilities and adapting to the technological development to increase the demands of the users of the General Facility and their needs, so that the service is upscale must work on the quality of services provided by the General Facility and provide all the factors and means to better serve. In order for these mechanisms to function properly, the use and application of electronic management, which is a mechanism for the development of management and the general facility, brings management closer to home, facilitates administrative transactions and works to improve the public service. Par rapport aux sanctions pénales, elle sont des crées suite au non respect de cet principe là. Elles sont des sanctions appliquées sur toutes les personnes ordinaires et morales dont (prison-impôt-saisie-dissolution de la personne moral). Donc, le principe de la conservation du secret bancaire est créé pour le bien de l'agent qui ne doit pas répandre les secrets de l'établissement (ce que la banque possède ou d'autres informations quiconque), l'agent est visé par la loi Qui lui limite ses fonctions. Il reste de dire que certaines conditions générales de vente sont éliminatoires dans certains cas et autres selon les situations secondaires rangées par ces règles.
ماستر اداري
Keywords: الخدمة العمومية – الحكم الراشد – المرفق العمومي – الإدارة الإلكترونية; Public Service - Good Governance - Public Facility - Electronic Management